A Small Macroeconometric Model of the People's Republic of China - Duo Qin; Marie Anne Cagas; Geoffrey Ducanes; Nedelyn Magtibay-Ramos; Pilipinas Quising; Xin-Hua He; Rui Liu; Shi-Guo Liu (Asian Development Bank (ADB), 2006)
This paper describes a quarterly macroeconometric model of the economy of People's Republic of China. The model comprises household consumption, investment, government, trade, production, prices, money, and employment blocks. The equilibrium-correction form is used for all the behavioral equations and the general simple dynamic specification approach is adopted in order to ensure the best possible blend of a priori long-run theories with a posteriori identified short-run factors, as well as country-specific features. The tracking performance of the model is evaluated. Forecasting and empirical investigation of a number of topical macroeconomic issues utilizing model simulations have shown the model to be immensely useful.
hdl:11540/1876
Keywords: 330; Wirtschaftslage; Wirtschaftspolitik; Öffentlicher Haushalt; Makroökonometrie; China